2008
DOI: 10.1117/12.793147
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced confocal microscopy imaging of the in-plane switching of cholesteric liquid crystal cells

Abstract: The recently developed fluorescence confocal polarizing microscopy (FCPM) imaging technique allows 3D images of the director structure in a liquid crystal cell to be resolved with sub-micron resolution. Results are presented on imaging the response of 5-micron pitch cholesteric liquid crystals to an in-plane electric field applied between two silver electrodes. The results show, in exquisite detail, how the application of an in-plane field causes the cholesteric helix to tilt through 90° either within, or imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Theoretical estimates of the expected shift in the reflection band gap based on the critical field for a given CLC material and the spatial variation of electric field in the cell are found to be in good agreement with the complex behavior observed experimentally. Jewell and Sambles [23,24] have used fluorescence confocal polarizing microscopy to visualize the change in helical structure under the effect of an electric field in three dimensions and have found that, at least in certain field strength ranges, the behavior of the cholesteric helix was not uniform in the cell and that the region in which the helix was unwound increased in size with increasing field magnitude. and a transformation from a chiral nematic to a nematic liquid crystalline order takes place (homogenous alignment with n j j E, where n is the director).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical estimates of the expected shift in the reflection band gap based on the critical field for a given CLC material and the spatial variation of electric field in the cell are found to be in good agreement with the complex behavior observed experimentally. Jewell and Sambles [23,24] have used fluorescence confocal polarizing microscopy to visualize the change in helical structure under the effect of an electric field in three dimensions and have found that, at least in certain field strength ranges, the behavior of the cholesteric helix was not uniform in the cell and that the region in which the helix was unwound increased in size with increasing field magnitude. and a transformation from a chiral nematic to a nematic liquid crystalline order takes place (homogenous alignment with n j j E, where n is the director).…”
Section: Introductionmentioning
confidence: 99%
“…Because of electric field variations, the response of the CLC in IDE cells can be rather complex. Jewell and Sambles [23,24] have used fluorescence confocal polarizing microscopy to visualize the change in helical structure under the effect of an electric field in three dimensions and have found that, at least in certain field strength ranges, the behavior of the cholesteric helix was not uniform in the cell and that the region in which the helix was unwound increased in size with increasing field magnitude. Xianyu et al [18] reported broadening of the reflection band and a decrease in the maximum reflectance with increasing field strength; they attributed these features to the non-uniformity of the electric field.…”
Section: Introductionmentioning
confidence: 99%